Architecture of integrated navigation systems with enhanced coordinate accuracy and fault detection - Dolintse, B.I. (Problems of Informatization and Management, 2023)
The integration of GNSS/INS is becoming increasingly pivotal for the precise operation of uncrewed aerial vehicles, especially in agriculture. This integration is underscored by two primary necessities: the assurance that after prolonged operation, the accuracy of the navigation parameters remains uncompromised and the implementation of an integrated navigation algorithm that is both straightforward and dependable, demanding minimal processing power from the onboard chips. This article first introduces the centralized Kalman filter approach, employed to merge GPS and INS systems, based on a loosely coupled framework. This amalgamation is streamlined, significantly curtailing the computational demands of the system, and reducing its intricacy. Subsequently, the discrepancies in the INS system’s navigation parameters, as gauged by the discrete Kalman filter algorithm, are rectified using a feedback amendment method. This strategy effectively counters the degradation in navigational accuracy that typically ensues from extended operational periods.